2014
DOI: 10.1055/s-0034-1367285
|View full text |Cite
|
Sign up to set email alerts
|

Activation of endocannabinoid system is associated with persistent inflammation in human aortic aneurysm

Abstract: Human aortic aneurysms have been associated with inflammation and vascular remodeling. Since the endocannabinoid system modulates inflammation and tissue remodeling, we investigated its components in human aortic aneurysms. We obtained anterior aortic wall samples from patients undergoing elective surgery for aortic aneurysm or coronary artery disease as controls. Histological and molecular analysis (RT-qPCR) was performed, and endocannabinoid concentration was determined using LC-MRM. Patient characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
3
1
Order By: Relevance
“…These results suggested that TRPV1 has a protective effect in cardiovascular diseases. Although one study demonstrated that TRPV1 expression was increased in patients with ascending aortic aneurysm, which seemed to be contradictory with our results [27], it should be noted that the origin of VSMCs in the ascending aorta was different from the abdominal aorta [28]. Nogi M et al reported that disruption and degradation of medial elastic lamina in the ascending aorta were more severe in ApoE −/-SmgGDS ± mice compared with ApoE −/mice after AngII infusion for 4 weeks.…”
Section: Discussioncontrasting
confidence: 99%
“…These results suggested that TRPV1 has a protective effect in cardiovascular diseases. Although one study demonstrated that TRPV1 expression was increased in patients with ascending aortic aneurysm, which seemed to be contradictory with our results [27], it should be noted that the origin of VSMCs in the ascending aorta was different from the abdominal aorta [28]. Nogi M et al reported that disruption and degradation of medial elastic lamina in the ascending aorta were more severe in ApoE −/-SmgGDS ± mice compared with ApoE −/mice after AngII infusion for 4 weeks.…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, there are recent studies that link increased 2-AG levels with worsening of inflammation. 37 , 38 It is possible that increased tissue levels of 2-AG may lead to activation of CB 1 receptor, hence causing a trend toward worsening inflammation; however, this mechanism has not been established in renal IRI. Given that indices of renal inflammation and oxidative stress remain unchanged, our findings support the notion that the modest improvement in renal function observed with enhanced 2-AG levels may be related to effects independent of its role in inflammation and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The mentioned data provide evidence on the activation of ECS in human aortic aneurysms associated with chronic inflammation and vascular remodeling. 53 Recent evidence shows there are interactions between the RAAS system and the ECS, suggesting AEA and 2-AG can regulate vascular contraction caused by Ang II, which can occur independently of the CB 1 receptor. This process is of great importance since, for example, increasing vascular sensitivity to Ang II is a marker of eclampsia.…”
Section: Side Effects Of Anandamide and Other Endocannabinoid At Vascmentioning
confidence: 99%
“…The mentioned data provide evidence on the activation of ECS in human aortic aneurysms associated with chronic inflammation and vascular remodeling. 53…”
Section: Side Effects Of Anandamide and Other Endocannabinoid At Vascmentioning
confidence: 99%